SOSIALISASI PENGGUNAAN INTERNET YANG SEHAT DAN AMAN UNTUK PKK RT 19/RW04 JANTURAN YOGYAKARTA - Dwi Setyowati (LPPM IST AKPRIND Yogyakarta, 2021)
he internet is indeed a very broad presenter of information. Technologicalsophistication is not always positive but can also have a negative impact. Therefore, asparents, we must be vigilant and play an active role in overseeing the internet activity offamily members.The aim of this socialization is the education process by providing sufficientunderstanding of the wise use of the internet so as to maximize the positive impacts of theinternet and minimize the negative impacts of surfing, so as to create an intelligent andproductive society. In this socialization the steps to support the creation of a healthy internetand how to use social media wisely are presentedIn accessing the internet will certainly add insight to everyone. But it must also berealized, that the misuse of information technology can place a person in danger or threatenthe integrity of the community.